2020
DOI: 10.1016/j.ibror.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-pinene and dizocilpine (MK-801) attenuate kindling development and astrocytosis in an experimental mouse model of epilepsy

Abstract: Understanding the molecular and cellular mechanisms involved during the onset of epilepsy is crucial for elucidating the overall mechanism of epileptogenesis and therapeutic strategies. Previous studies, using a pentylenetetrazole (PTZ)-induced kindling mouse model, showed that astrocyte activation and an increase in perineuronal nets (PNNs) and extracellular matrix (ECM) molecules occurred within the hippocampus. However, the mechanisms of initiation and suppression of these changes, remain unclear. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 82 publications
0
15
0
Order By: Relevance
“…Yang et al (2016) reported that the oral administration of the α‐pinene (12.5–200 mg/kg) prior to pentobarbital (45 mg/kg) reduced sleep latency. It is reported that α‐pinene may prevent epileptic seizures by suppressing astrocyte activation and extracellular matrix molecule production (Ueno et al, 2020). α‐pinene has a low molecular weight and high lipophilicity and by high permeability reaches to the brain and induces its physiological effects such as anxiolytic, antioxidant and anti‐seizure by altering GABAergic and NMDA receptors in the hippocampus (Ueno et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yang et al (2016) reported that the oral administration of the α‐pinene (12.5–200 mg/kg) prior to pentobarbital (45 mg/kg) reduced sleep latency. It is reported that α‐pinene may prevent epileptic seizures by suppressing astrocyte activation and extracellular matrix molecule production (Ueno et al, 2020). α‐pinene has a low molecular weight and high lipophilicity and by high permeability reaches to the brain and induces its physiological effects such as anxiolytic, antioxidant and anti‐seizure by altering GABAergic and NMDA receptors in the hippocampus (Ueno et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Pinene (C 10 H 16 ) is a bicyclic, double bond, terpenoid hydrocarbon and two isoforms (α and β) found in nature, for example, in pine (coniferous trees) essential oils. α‐pinene is widely used as a food flavouring ingredient and has been approved as a safe food additive by the U.S. Food and Drug Administration (FDA) (Ueno et al, 2020). These two phytochemicals have several biological activities such as fungicidal, antibacterial, anticancer and anti‐nociceptive (Kumar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, water could also be obtained. After In(OTf ) 3mediated tautomerization, the indium-chelated enol moiety of G could react with molecular oxygen (from the air) to lead to H. Finally, the cleavage of the intramolecular oxygen-oxygen bond of the resulting (TfO) 2 In-conjugated peroxide moiety with the six-membered ring was the driving force that triggered the deprotonation of the α-proton, producing 6a via the formation of a carbon-oxygen double bond (red). After the recombination of TfOInvO and two molecules of TfOH, water was generated and In(OTf ) 3 was recovered for the next catalytic cycle under the overall Friedel-Crafts conditions.…”
Section: Papermentioning
confidence: 99%
“…Herein, we summarize the recent published findings on the biological and pharmacological activities of pinene (Table 1 (Tab. 1) ; References in Table 1: Bouzenna et al, 2017[ 3 ]; Cardoso et al, 2020[ 4 ]; Chen et al, 2015[ 5 ]; de Macêdo et al, 2018[ 6 ]; do Amaral et al, 2020[ 7 ]; Ensaka and Sakamoto, 2020[ 8 ]; Felipe et al, 2019[ 10 ]; Govindarajan et al, 2016[ 11 ]; Hou et al, 2019[ 12 ]; İnce et al, 2018[ 13 ]; Jensen et al, 2020[ 14 ]; Jo et al, 2021[ 15 ]; Karthikeyan et al, 2018[ 17 ], 2019[ 16 ]; Kasuya et al, 2015[ 18 ]; Khoshnazar et al, 2019[ 19 ], 2020[ 20 ]; Kim et al, 2015[ 21 ]; Kovač et al, 2015[ 22 ]; Kusuhara et al, 2019[ 23 ]; Langsi et al, 2020[ 24 ]; Lee et al, 2017[ 25 ]; Li et al, 2016[ 28 ]; Memariani et al, 2017[ 29 ]; Meng et al, 2020[ 30 ]; Min et al, 2020[ 32 ]; Moreira et al, 2016[ 33 ]; Nóbrega et al, 2020[ 34 ]; Pajaro-Castro et al, 2017[ 35 ]; Pinheiro et al, 2015[ 36 ]; Porres-Martínez et al, 2016[ 37 ]; Rodrigues et al, 2015[ 39 ]; Šimunović et al, 2020[ 41 ]; Ueno et al, 2019[ 44 ], 2020[ 43 ]; Wang et al, 2019[ 46 ]; Xu et al, 2018[ 47 ]; Yang et al, 2016[ 48 ]; Zamyad et al, 2019[ 50 ]; Zhang et al, 2015[ 52 ], 202[ 51 ]0; Zhao et al, 2018[ 53 ]).…”
mentioning
confidence: 99%